ChemInform Abstract: Thermoelectric Plastics: From Design to Synthesis, Processing and Structure—Property Relationships. Issue 51 (5th December 2016) - Kroon, Renee; Mengistie, Desalegn Alemu; Kiefer, David; Hynynen, Jonna; Ryan, Jason D.; Yu, Liyang; Mueller, Christian
Abstract: Review: 51 refs.